Spontaneität und Ich bei Fichte (und Kant) - Gaspar, Francisco Prata (Studia Kantiana, 2023)
The aim of the article is to comment the main concept "I" in Kant and Fichte by analyzing the use of the term "spontaneity" in such authors. The starting point of the article is that the understanding of "spontaneity" throws light in the "I" concept on aspects from its structure that usually remain in the shadow, because usually just the articulate and complex self-relation was taken into account. The article tries first to analyze selected Kant’s passages on spontaneity and I, in order to discuss these concepts such as they appear in the first principle of the doctrine of science, as it is formulated in its first presentation (GWL).